2016
DOI: 10.1007/s12576-016-0496-6
|View full text |Cite
|
Sign up to set email alerts
|

BDNF levels are increased in peripheral blood of middle-aged amateur runners with no changes on histone H4 acetylation levels

Abstract: Our aim was to compare the basal levels of plasma brain-derived neurotrophic factor (BDNF) and global histone H4 acetylation in peripheral blood mononuclear cells (PBMCs) of healthy amateur runners (EXE group) with sedentary individuals (SED group) as well as to investigate the acute effect of a running race on these markers in the EXE group. Five days before the race, all participants were submitted to a basal blood collection. On the race day, two blood samples were collected in the EXE group before the runn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…The current study data corroborates those obtained by Zoladz et al (21) who showed that basal plasma BDNF levels were higher in young, well-trained athletes including sprinters, jumpers, and runners, compared with untrained participants. In agreement, da Silveira et al (30) also showed that plasma BDNF levels increased in middle-aged amateur runners compared to the sedentary group.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The current study data corroborates those obtained by Zoladz et al (21) who showed that basal plasma BDNF levels were higher in young, well-trained athletes including sprinters, jumpers, and runners, compared with untrained participants. In agreement, da Silveira et al (30) also showed that plasma BDNF levels increased in middle-aged amateur runners compared to the sedentary group.…”
Section: Discussionsupporting
confidence: 71%
“…In this sense, the current study was the first to show that exercise modulates the acetylation status in the elderly people, indicating that histone H4 acetylation can be considered as a novel biomarker that reacts epigenetically to physical activity in this population. On the other hand, a recent study (30) reported no difference in histone H4 acetylation levels between middle-aged runners and sedentary individuals. These findings were in agreement with the experimental studies reporting that histone acetylation status in response to exercise might act in an age-dependent manner (8,36).…”
Section: Discussionmentioning
confidence: 78%
“…Immediately following LTP recordings, some animals were sacrificed by rapid decapitation, and the hippocampus was removed and immediately frozen in liquid N 2 . The western blotting method was performed as in previous study procedures [29,51,52].…”
Section: Western Blottingmentioning
confidence: 99%
“…Additionally, BDNF is essential to regulation of activity-dependent pre-synaptic vesicle cycling, which is dependent on N-methyl D-aspartate (NMDA) receptor activation in cultured neocortical neurons from BDNF-knockout mice [27]. Furthermore, increasing of BDNF is associated with enhancing of NMDA expression and intracellular calcium concentrations [28,29], thereby promoting long-term changes to synaptic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, BDNF can cross the blood-brain barrier in a bidirectional manner, as well it was also reported that the peripheral levels of this neurotrophin seem to present a strong correlation with cerebrospinal fluid levels [8]. Therefore, plasma BDNF levels have been used as a biomarker in several clinical studies [9][10][11]. In view of all these considerations, strategies that modulate peripheral levels of BDNF should be consider important tools among elderly.…”
Section: Introductionmentioning
confidence: 97%